K-POP NON-KOREA BUKAN APROPRIASI BUDAYA : ANALISIS WACANA KRITIS MODEL TEUN VAN DIJK - Dwi Windah Wulansari (sarasvati, 2020)
This research supports the structure of critical discourse when viewed from the perspective of Teun Van Dijk. The data source used was a video uploaded by the Indonesian representative entitled K-POP Non Korea EXP Edition. The method used is descriptive qualitative. The results of the analysis show that non-Koreans can be part of K-pop. Various pros and cons experienced by this EXP EDITION boy band, did not ignite their enthusiasm for a career in South Korea. The phenomenon in this EXP EDITION. Positive and negative opinion. Most of the supporters of this boy band because they see their efforts are not instantaneous as previously reported. Some consider that they are giving up Korean culture or what is cooler is called cultural appropriation. Associated with the practice of power and discourse accents. The practice of power in this non-Korean K-pop phenomenon. Reporting from the Columbia University official website, Bora Kim formed the EXP EDITION group and mapped it out with the aim of "discussing what Kpop and Kpop fandom are".